Cocaine Enhances HIV-1 Transcription in Macrophages by Inducing p38 MAPK Phosphorylation - Swepson, Chelsie; Ranjan, Alok; Balasubramaniam, Muthukumar; Pandhare, Jui; Dash, Chandravanu (Frontiers in Microbiology, 2016)
Cocaine is a commonly used illicit drug among HIV-1 infected individuals and is known to increase HIV-1 replication in permissive cells including PBMCs, CD4+ T cells, and macrophages. Cocaine’s potentiating effects on HIV-1 replication in macrophages- the primary targets of the virus in the central nervous system, has been suggested to play an important role in HIV-1 neuro-pathogenesis. However, the mechanism by which cocaine enhances HIV-1 replication in macrophages remain poorly understood. Here we report the identification of cocaine-induced signaling events that lead to enhanced HIV-1 transcription in macrophages. Treatment of physiologically relevant concentrations of cocaine enhanced HIV-1 transcription in a dose-dependent manner in infected THP-1 monocyte-derived macrophages (THP-1macs) and primary monocyte-derived macrophages (MDMs). Towards decoding the underlying mechanism, results presented in this report demonstrate that cocaine induces the phosphorylation of p38 mitogen activated protein kinase (p38 MAPK), a known activator of HIV-1 transcription. We also present data suggesting that the p38 MAPK-driven HIV-1 transcription is dependent on the induction of mitogen- and stress-activated protein kinase 1 (MSK1). Consequently, MSK1 mediates the phosphorylation of serine 10 residue of histone 3 (H3 Ser10), which is known to activate transcription of genes including that of HIV-1 in macrophages. Importantly, our results show that inhibition of p38 MAPK/MSK1 signaling by specific pharmacological inhibitors abrogated the positive effect of cocaine on HIV-1 transcription. These results validate the functional link between cocaine and p38 MAPK/MSK1 pathways. Together, our results demonstrate for the first time that the p38 MAPK/MSK1 signaling pathway plays a critical role in the cocaine-induced potentiating effects on HIV-1 infection, thus providing new insights into the interplay between cocaine abuse and HIV-1 neuro-pathogenesis.